Pemberdayaan Kelompok Usaha Galansia melalui Teknologi Tepat Guna dan Digital Marketing - Aprinawati Aprinawati; Hidir Efendi; Haryadi Haryadi; Khafi Puddin; Fadli Agus Triansyah; Nasywa Khalista; Fadillah Fasha; Apriansyah Sipayung (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to empower the Galansia Business Group in Sait Buttu Saribu Village, Pematang Sidamanik District, Simalungun Regency, which is engaged in the processing of agricultural products and household products. The main problems faced by the partners include limited production capacity, inconsistent product quality, simple business management, and traditional marketing methods. To overcome these problems, the community service team applied a participatory approach by providing appropriate technology, business management assistance, and digital marketing training. The results of the activities showed a significant increase in production capacity, time efficiency, and product quality consistency thanks to the use of onion slicing machines and liquid soap mixing machines. In terms of marketing, the partners successfully utilized social media as a means of promotion and distribution, and improved product packaging to make it more attractive and professional. In terms of management, the partners were able to implement simple digital-based financial records and were facilitated in handling business legality. The impact achieved was an increase in members' income of more than 50% and the growth of entrepreneurial spirit among the village's elderly. This program has proven to be effective in supporting business independence and can be used as a model for community-based MSME empowerment in the digital era.